Security Practices in Agile Development: An Industry Survey on Adoption, Perceived Impact, and Measurement in DevOps - Selva-Mora, Alejandra; Quesada-López, Christian; Lara, Adrián; Jenkins, Marcelo (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2026: Anais do XXIX Congresso Ibero-Americano em Engenharia de SoftwareDO - 10.5753/cibse.2026.42452, 2026)
This paper presents an empirical survey study (N=24) examining the integration of security practices into agile and continuous development processes. The findings reveal that while the most adopted practices include Standards and Requirements (71%), Code Review (67%), and Compliance and Policy (63%), their implementation remains predominantly non-systematic. Despite moderate to high perceived impact, significant gaps exist between recognition and effective adoption, compounded by low security expert participation (37%) and a notable scarcity of metrics. The findings provide exploratory evidence on the current state of practice and key priorities for organizations looking to strengthen security integration while maintaining agility in their development processes.